Keterbentukan Kepercayaan Pelanggan Shopee Melalui Kualitas Hubungan, Reputasi dan Keamanan Marketplace - Siti Nur Halizah; Allyana Infante; Didit Darmawan (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2022)
Currently, technological developments are sophisticated. Recent human development has been complemented by rapid changes in technological progress and an increase in the variety of digital services and devices. Advances in technology have always made it easier for humans to move quickly. In addition, the results obtained are also much more. The capacity to achieve technology, diffusion of innovation, generation of knowledge and creativity are the fundamental factors needed to provide economic growth and development as well as a sustainable competitive advantage. Marketplace has developed into a form of marketplace that emphasizes convenience, speed and product diversity. The barriers of distance and space have had an effective alternative solution. Marketplace is built and developed based on customer trust. This study aims to determine the role of relationship quality, reputation and security of the Shopee marketplace on customer trust. The population of this study is aimed at customers from Shopee in Manila City in the Philippines. The sample of this study used 177 respondents. In this study, three independent variables and one dependent variable were used. The analysis technique uses multiple linear regression. This study proves that the reputation and security of the marketplace have a significant effect on customer trust. Likewise, the quality of the relationship has a significant effect on customer trust.